Using AGREE II reporting checklist to evaluate the quality of Tuina clinical practice guidelines - Huang, Fan; Zhang, Yue; Huang, Chuyu; Qiu, Mingwang; Zhao, Siyi; Liang, Junquan; Fan, Zhiyong; Wu, Shan (Frontiers in Medicine, 2023)
Objective To evaluate the methodological quality of Tuina clinical practice guidelines. Methods Computer searches of China National Knowledge Infrastructure (CNKI), Chinese Technical Periodicals (VIP), Wanfang Data Knowledge Service Platform, PubMed, Cochrane Library, Embase, and other databases were conducted to search for published guidelines on Tuina, with a search time frame from database creation to March 2021. Four evaluators independently used the Appraisal of Guidelines for Research and Evaluation II instrument to evaluate the quality of the included guidelines. Results Eight guidelines related to Tuina were included in this study. The quality of reporting was low in all included guidelines. The highest quality report had a total score of 404 and was rated as "highly recommended". The worst guideline had a final score of 241 and was rated as "not recommended". Overall, 25% of the included guidelines were recommended for clinical use, 37.5% were recommended after revision, and 37.5% were not recommended. Conclusion The number of existing Tuina clinical practice guidelines is limited. The methodological quality is low, far from the internationally accepted clinical practice guideline development and reporting norms. In the future, reporting specifications of guidelines and the methodology of guideline development, including the rigor of the guideline development process, the clarity, application, and independence of reporting, should be emphasized in the development of Tuina guidelines. These initiatives could improve the quality and applicability of clinical practice guidelines to guide and standardize the clinical practice of Tuina.